A highly sensitive and selective spectrofluorimetric method for the determination of molybdenum at pico-trace levels in various matrices using N-(pyridin-2-yl)-quinoline-2-carbothioamide - Ahmed, Muhammad Jamaluddin; Afrin, Ayesha; Haque, Muhammad Emdadul (European Journal of Chemistry, 2021)
A new spectrofluorimetric reagent N-(pyridin-2-yl)-quinoline-2-carbothioamide (PQTA) has been synthesized and characterized. A very simple, ultra-sensitive, and highly selective, and non-extractive new spectrofluorimetric method for the determination of molybdenum at pico-trace levels using PQTA has been developed. This novel fluorimetric reagent PQTA, becomes oxidized in a slightly acidic (0.0025-0.05 M H2SO4) solution with molybdenum (VI) in absolute ethanol to produce a highly fluorescent oxidized product (λex = 300 nm; λem= 377 nm). Constant and maximum fluorescence intensities were observed over a wide range of acidity (0.0025-0.0500 M H2SO4) for the period between 2 min and 24 h. Linear calibration graphs were obtained for 0.001-600 μg/L of Mo having a detection limit of 0.15 ng/L; the quantification limit of the reaction system was found to be 1.5 ng/L and the RSD was 0-2%. A large excess of over 60 cations, anions, and complexing agents like chloride, phosphate, azide, tartrate, oxalate, and SCN- etc. do not interfere in the determination. The developed method was successfully used in the determination of molybdenum in several Certified Reference Materials (Alloys, steel, serum, bovine liver, drinking water, soil, and sediments) as well as in some environmental waters (Potable and polluted), biological fluids (Human blood, urine, hair, and milk), soil samples and food samples (Vegetables, rice, and wheat) solutions containing both molybdenum (VI) and molybdenum (V) ions. The results of the proposed method for assessing biological, food and vegetable samples were comparable with ICP-OES and AAS were found to be in excellent agreement.